2017
DOI: 10.1186/s40729-017-0097-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of alveolar ridge augmentation with individualized CAD-CAM-produced titanium mesh

Abstract: BackgroundThe augmentation of the jaw has been and continues to be a sophisticated therapy in implantology. Modern CAD-CAM technologies lead to revival of old and established augmentation techniques such as the use of titanium mesh (TM) for bone augmentation. The aim of this retrospective study was to evaluate the clinical outcome of an individualized CAD-CAM-produced TM based on the CT/DVT-DICOM data of the patients for the first time.MethodsIn 17 patients, 21 different regions were augmented with an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
121
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(130 citation statements)
references
References 26 publications
9
121
0
Order By: Relevance
“…In conclusion, tension release was very important to prevent Ti‐mesh exposure, which could be achieved via optimizing incision design, tension‐free flap preparation, indication selection, and the properties like thickness of Ti‐mesh. In this study, Ti‐mesh exposure at the second week did not have significant positive effect on the osteogenetic process underneath the L‐shaped Ti‐mesh, which was in accordance with Sagheb's study . According to the literature, usually an early exposure within the first weeks showed negative impacts on bone regeneration comparing late exposure …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In conclusion, tension release was very important to prevent Ti‐mesh exposure, which could be achieved via optimizing incision design, tension‐free flap preparation, indication selection, and the properties like thickness of Ti‐mesh. In this study, Ti‐mesh exposure at the second week did not have significant positive effect on the osteogenetic process underneath the L‐shaped Ti‐mesh, which was in accordance with Sagheb's study . According to the literature, usually an early exposure within the first weeks showed negative impacts on bone regeneration comparing late exposure …”
Section: Discussionsupporting
confidence: 90%
“…The titanium mesh exposure is a common complication, the exposure rates for most studies were about 30% and even higher than that. For example, Sagheb et al reported that CAD/CAM Ti‐mesh exposure occurred in 33% of the augmented sites during the healing period. Sumida et al compared the exposure rate of CAD designed custom‐made Ti‐meshes and commercial Ti‐meshes, mucosal rupture occurs for 7.7% in the custom‐made group and 23.1% in the conventional group, which demonstrated better results for custom‐made group but there was not significant difference between the two group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upper soft connective tissue did not infiltrate downwards in the groups with and without membrane. If the polymer is given a resilience that can be used as a membrane through tissue engineering process and 3D‐printed as a defect‐specific membrane, it may perform the function of space making frame with macro‐porosity like titanium mesh . The previous study compared PCL membrane with collagen membrane in beagle model .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the principles of the GBR technique, individualized titanium meshes are proposed to overcome the problems of the conventional titanium meshes [13]. Literature [14][15][16] reveals the advantages of this technology such as a shortened and facilitated surgery time in sense of a modern digital work-flow. Although Sumida et al evaluated less exposures, but not statistically significant, in patient-specific titanium meshes [17], soft tissue management remains one of the most challenging targets in customized bone regeneration [18].…”
Section: Introductionmentioning
confidence: 99%